Batik Trusmi Cirebon's Online Promotion Strategy to Increase Sales Through Instagram @btbatiktrusmi in 2024 - Irfan Irfan Dwi Hermawan; Suciati (Jogjakarta Communication Conference (JCC), 2026)
Promotional strategies through social media are a crucial aspect of digital marketing communications, particularly for the batik industry facing competition in the digital era. This study aims to describe the online promotional strategy implemented by Batik Trusmi Cirebon through its Instagram handle @btbatiktrusmi throughout 2024 and to analyze the response and engagement levels of followers to published promotional content. This study employed a qualitative descriptive method. Data collection techniques included documentation and in-depth interviews. Purposive sampling was employed to obtain informants aligned with the research objectives: marketing managers, marketing staff, and Trusmi batik consumers. Data validity was tested using source triangulation to ensure the validity of the information obtained. The results showed that the promotional strategy was implemented through the use of hard-selling, educational, and branding content tailored to the productive age market segment (25 years and older). Instagram insight analysis was used to identify audience population, interests, viewing duration, and interaction levels such as likes, comments, and shares. Online data is then compared with offline sales data to identify the most potential market segments. This strategy demonstrates that optimally utilizing Instagram features can increase engagement and contribute to increased product sales. The implementation of the promotion mix on Instagram includes advertising through Meta Ads (ads awareness and ads hard selling), public relations through educational and responsive content, sales promotion through certain period promos, direct marketing through comment and direct message features, and event marketing through offline event promotions published on Instagram.